PENDIDIKAN RUQYAH SYAR’IYYAH: DAMPAKNYA TERHADAP AKHLAK DAN ETIKA MASYARAKAT - Rudi Iskandar (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
Ruqyah Shari’yyah education is part of the solution for humanity in addressing the weak behavior of individuals in relating to one another. Ruqyah Shari’yyah, exemplified by Prophet Muhammad (PBUH), serves as a solution to improve human moral and ethical behavior. As a result, people are able to respect one another, speak kindly, be honest, and take responsibility in fulfilling trusts. Various holy texts, the sayings of Prophet Muhammad (PBUH), and books written by scholars that reference the Prophet’s treatments indicate that his medicinal practices are natural remedies effective for healing the body and soul, transforming bad behavior into good, and fostering morality and ethics. Ruqyah sharia is not only a treatment solution but also a holistic spiritual therapy that focuses on cleansing the heart and strengthening faith. By removing spiritual barriers and reinforcing the connection with Islamic teachings, ruqyah indirectly becomes an effective solution in transforming a person's morals and ethics from blameworthy to praiseworthy (Akhlaqul Karimah).